Pain Reconceptualisation after Pain Neurophysiology Education in Adults with Chronic Low Back Pain: A Qualitative Study - Richard King; Victoria Robinson; Helene L. Elliott-Button; James A. Watson; Cormac G. Ryan; Denis J. Martin (Pain Research and Management)
Pain neurophysiology education (PNE) is an educational intervention for patients with chronic pain. PNE purports to assist patients to reconceptualise their pain away from the biomedical model towards a more biopsychosocial understanding by explaining pain biology. This study aimed to explore the extent, and nature, of patients’ reconceptualisation of their chronic low back pain (CLBP) following PNE. Eleven adults with CLBP underwent semistructured interviews before and three weeks after receiving PNE. Interviews were transcribed verbatim and thematically analysed in a framework approach using four a priori themes identified from our previous research: (1) degrees of reconceptualisation, (2) personal relevance, (3) importance of prior beliefs, and (4) perceived benefit of PNE. We observed varying degrees of reconceptualisation from zero to almost complete, with most participants showing partial reconceptualisation. Personal relevance of the information to participants and their prior beliefs were associated with the degree of benefit they perceived from PNE. Where benefits were found, they manifested as improved understanding, coping, and function. Findings map closely to our previous studies in more disparate chronic pain groups. The phenomenon of reconceptualisation is applicable to CLBP and the sufficiency of the themes from our previous studies increases confidence in the certainty of the findings.